Conﬁgurational splitting in Raman scattering spectra of crystals with the order-disorder type phase transitions - Stasyuk, I.V.; Ivankiv, Ya.L. (Condensed Matter Physics, 1999)
A system of equations for the averaged phonon Green function determining the shapes of the lines in Raman scattering spectra is obtained in the
coherent potential approximation. Conﬁgurationally split components of the
Raman scattering are studied within a simple model. For the KH₂PO₄ and
the CsH₂PO₄-type ferroelectrics the possibility to observe the conﬁgurational splitting experimentally is discussed. В наближенні когерентного потенціалу одержана система рівнянь
для усередненої фононної функції Гріна, що визначає профілі ліній в
спектрах Рамана. На прикладі простої моделі проведено дослідження конфігураційно розщеплених компонент раманівських ліній. Для
сегнетоелектриків типу KH₂PO₄ та CsH₂PO₄ обговорюється питання
про можливий експериментальний вияв конфігураційного розщеплення.